Pengaruh Kepuasan Kerja, Komitmen Efektif, Dan Stress Kerja Terhadap Turnover Intention Pada Pramuniaga/Pramuniagi PT Circleka Indonesia Utama Cabang Yogyakarta - Husni Tamrin (EBBANK, 2020)
This study aims to determine the effect of job satisfaction, effective commitment, and work stress on turnover intention.The variables of this study are job satisfaction, effective commitment, and work stress on turnover intention. The population in this study was a saleswoman at PT Circleka Indonesia Utama Yogyakarta Branch. The technique of this research sample used Slovin method and obtained 95 respondents, the sampling technique used incidental sampling, the data collection method used a questionnaire. While the data analysis technique uses multiple linear regression analysis supported by t test, determinant coefficient, and classical assumption test consisting of normality test, heteroscedasticity test, and multicollinearity test.The results showed that job satisfaction had no effect on turnover intention, effective commitment had no effect on turnover intention. And work stress has a significant positive effect on turnover intention